Stereoselective Synthesis of Euscapholide and Tetraketide via Prins Cyclisation and Ring-Closing Metathesis - Biradar, Dhanraj O.; Mane, Yogesh D.; Subba Reddy, Basi V. (SynOpen, 2022)
A concise and diastereoselective total synthesis of tetraketide and euscapholide is described in ten steps in 10.6% overall yield from acetaldehyde and (S)-pent-4-ene-1,2-diol. Jacobsen hydrolytic kinetic resolution, Prins cyclization, ring-closing metathesis and oxa-Michael addition reactions are the key steps involved in the synthesis.
Keywords: Prins cyclization; euscapholide; tetraketide; ring-closing metathesis